SHM_1308310_HST_3D Thin-Butted Stone Axe - National Historical Museums (National Historical Museums, 2026)
A structured light 3D model of a thin-butted stone axe from the Swedish Early or Middle Neolithic, collected from Hjelmsäter in Örebro and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=395

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C1B6E7C6-5045-46B5-8F24-98107AAE255A
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; 3D Model; Dynamic Collections; Museum Object; Hjelmsäter; Swedish Neolithic; Structured Light Scanning; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi